2000
DOI: 10.1074/jbc.275.13.9251
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism by Which Phosphonoformic Acid Resistance Mutations Restore 3′-Azido-3′-deoxythymidine (AZT) Sensitivity to AZT-resistant HIV-1 Reverse Transcriptase

Abstract: The development of phosphonoformic acid (PFA) resistance against a background of 3-azido-3-deoxythymidine (AZT) resistance in human immunodeficiency virus type 1 (HIV-1) restores viral sensitivity to AZT. High level AZT resistance requires multiple mutations (D67N/K70R/T215F/K219Q). In order to characterize the mechanism of PFA resistance-mediated resensitization to AZT, the A114S mutation associated with PFA resistance was introduced into the reverse transcriptase (RT) of both wild type and drug-resistant vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 25 publications
3
54
0
Order By: Relevance
“…The NRTI-MP excision activities of WT, K65R, and K70E HIV-1 RT were investigated by measuring the abilities of WT or mutant RT to excise AZT-MP, 3TC-MP, CBV-MP, or TNV from the 3Ј terminus of the primer and to rescue DNA synthesis, as described previously (2). Excision assays were carried out using either ATP or pyrophosphate as the phosphate donor ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NRTI-MP excision activities of WT, K65R, and K70E HIV-1 RT were investigated by measuring the abilities of WT or mutant RT to excise AZT-MP, 3TC-MP, CBV-MP, or TNV from the 3Ј terminus of the primer and to rescue DNA synthesis, as described previously (2). Excision assays were carried out using either ATP or pyrophosphate as the phosphate donor ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For 3TC-MP excision assays, 1 M dCTP, 1 M TTP, and 5 M ddATP were included in the reaction mixture. After defined incubation periods, aliquots were removed and processed as described previously (2).…”
Section: Methodsmentioning
confidence: 99%
“…W88G, E89K, A114S, S117T, Q161L, and M164I) (56,57) and with the deletion of Thr 69 , which is often associated with the Q151M complex (58 -60). All of those mutations increase HIV-1 susceptibility to AZT by reducing the phosphorolytic activity of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, mutations associated with PFA resistance were shown to increase susceptibility to the nucleoside analogue 3Ј-azido-3Ј-deoxythymidine (zidovudine or AZT) (10, 11). Biochemical data have shown that PFA-associated resistance mutations diminish the phosphorolytic excision of incorporated chain terminators such as 12). Wild type HIV-1 RT is capable of removing AZT-monophosphate in the presence of pyrophosphate (PP i ) (13), or a PP i donor such as ATP (14).…”
mentioning
confidence: 99%